Study of Multi-Service Networks and Communication Systems Using Distributed Network Technology in Mountain Areas - Rustamova D. F.; Mehdiyeva A. M.; Mahmudova Z. A.; Abdullaev J.; Sapaev B. (BIO Web of Conferences)
It should be noted that the development of the digital economy directly depends on the introduction of advanced technologies: nanotechnology, biotechnology, complex energy systems technologies, quantum technologies, etc. At the same time, it is difficult to imagine the further development of corporate multiservice networks and communication systems without the widespread introduction of innovative technologies in a single information telecommunication infrastructure. The interaction of corporate multiservice networks and innovative technologies allows you to create a virtual transport network, with the help of which you manage transmitted useful and service packages and provide services. The FN concept involves the introduction of virtualization technologies, artificial intelligence methods and tools on a corporate network. The article analyzes the characteristics of corporate multiservice networks and communication systems using the technology of building distributed communication networks. The characteristics of corporate multiservice networks and communication systems using the technology of building distributed communication networks are analyzed and investigated, and a mathematical model of quality of service is proposed taking into account the management of information and network resources. It was found that the integrated performance indicators of multiservice corporate networks are largely determined by the reliability, information security and quality of service of IP / MPLS switching nodes and the IMS-Internet Protocol Multimedia Subsystem multimedia communication system using the signaling system and protocols for providing multimedia services and establishing session sessions. Thus, the results of QoS & QoE quality of service research and an analysis of numerical calculations of the probability and time characteristics of corporate multiservice networks based on the architectural concept of NGN and FN using the concept of SDN, NFV and IMS, requires the study of complex performance indicators of multiservice enterprise networks.